Case report: Good response to CMOP regimen containing mitoxantrone hydrochloride liposome (PLM60) as induction chemotherapy in patients with angioimmunoblastic T-cell lymphoma - Liang, Lijie; Jiang, Ming (Frontiers in Oncology, 2024)
Angioimmunoblastic T-cell lymphoma (AITL) is a highly aggressive subtype of peripheral T-cell lymphoma. The current prognosis with the first-line standard of care remains unsatisfactory, necessitating the exploration of more effective treatment options. We reported 5 cases of AITL receiving CMOP (mitoxantrone hydrochloride liposome, cyclophosphamide, vincristine, and prednisone). Cases 1 and 2 initially received CHOP as first-line induction therapy but switched to CMOP due to inadequate efficacy and cardiac adverse events. Cases 3, 4, and 5 were newly diagnosed and received CMOP. All patients achieved complete remission with acceptable cardiotoxicities and hematologic toxicities. After study treatment discontinuation, Cases 1 and 3 underwent autologous stem cell transplantation, and Cases 4 and 5 received oral maintenance agents. At the last follow-up, 4 patients remained in remission and 1 (Case 2) exhibited tumor recurrence. CMOP showed promise as a potential treatment option for AITL patients. Further research is essential to identify its efficacy and safety.